2022
DOI: 10.1002/pld3.389
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of strigolactone receptor activity in a Nicotiana benthamiana dwarf14 mutant

Abstract: DWARF14 (D14) is an ɑ/β‐hydrolase and receptor for the plant hormone strigolactone (SL) in angiosperms. Upon SL perception, D14 works with MORE AXILLARY GROWTH2 (MAX2) to trigger polyubiquitination and degradation of DWARF53(D53)‐type proteins in the SUPPRESSOR OF MAX2 1‐LIKE (SMXL) family. We used CRISPR‐Cas9 to generate knockout alleles of the two homoeologous D14 genes in the Nicotiana benthamiana genome. The Nbd14a,b double mutant had several phenotypes that are consistent with the loss of SL perception in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 114 publications
(244 reference statements)
1
4
0
Order By: Relevance
“…In the present study, we found that the exogenous GR24 treatment at different concentrations (5 µmol/L, 10 µmol/L, and 20 µmol/L) promoted stem thickening in strawberry plants (Figure 1), which was consistent with previous research. In addition, after knocking out the SL receptor gene dwarf14 in Arabidopsis, the plants showed dwarfing and shortened petioles [37]. In our experiment, both the 5 µmol/L and 10 µmol/L GR24 treatments promoted plant height (Figure 2A,B) and petiole length in strawberry plants (Figure 2C,D).…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, we found that the exogenous GR24 treatment at different concentrations (5 µmol/L, 10 µmol/L, and 20 µmol/L) promoted stem thickening in strawberry plants (Figure 1), which was consistent with previous research. In addition, after knocking out the SL receptor gene dwarf14 in Arabidopsis, the plants showed dwarfing and shortened petioles [37]. In our experiment, both the 5 µmol/L and 10 µmol/L GR24 treatments promoted plant height (Figure 2A,B) and petiole length in strawberry plants (Figure 2C,D).…”
Section: Discussionsupporting
confidence: 52%
“…Then, the D14 ortholog in Arabidopsis thaliana , AtD14 was identified as well as the paralogous D14 family receptor KAI2 ( Waters et al 2012 ). Following these findings, an increasing number of studies identified and examined of SL-receptor function in many other plant species including chrysanthemum ( Wen et al 2015 ), Medicago ( Lauressergues et al 2015 ), barley ( Marzec et al 2016 ), poplar ( Zheng et al 2016 ), pea ( de Saint Germain et al 2016 ), soybean ( Ahmad et al 2020 ), cotton ( Wang et al 2019 ), lotus ( Carbonnel et al 2020 ), wheat ( Liu et al 2021 ), canola ( Stanic et al 2021 ), sugarcane ( Hu et al 2021 ), tobacco ( Li et al 2020 ; White et al 2022 ), and importantly in SL-induced parasitic plants such as Striga and Phelipanche ramosa ( Toh et al 2015 ; de Saint Germain et al 2021 ). Additionally, sequence analyses identified putative SL receptor homologs in 143 species and classified evolutionary sub-families within the larger α/β D14 family receptors including D14s and related butenolide receptors–KAI2s as well as DLK2s (D14-LIKE2) ( Bythell-Douglas et al 2017 ).…”
Section: Strigolactone Perception By D14 Family Proteinsmentioning
confidence: 99%
“…These proteins are specifically targeted by D14 and not by KAI2 (Wang et al 2015;Khosla et al 2020a;White et al 2022). Finally, SMXL3-and aSMXL4-clade proteins, represented by SMXL3, SMXL4, and SMXL5 in Arabidopsis, regulate phloem development and anthocyanin abundance (Cho et al 2018;Wallner et al 2017Wallner et al , 2023Wu et al 2017;Li et al 2024).…”
Section: Introductionmentioning
confidence: 99%
“…SMXL78-clade proteins, represented by SMXL6, SMXL7, and SMXL8 in Arabidopsis and D53 in rice, control axillary branching or tillering, secondary growth, leaf elongation, internode elongation, and more (Jiang et al 2013; Zhou et al 2013; Agusti et al 2011; Liang et al 2016; Wang et al 2020a; Yang et al 2020; de Saint Germain et al 2013; Li et al 2020). These proteins are specifically targeted by D14 and not by KAI2 (Wang et al 2015; Khosla et al 2020a; White et al 2022). Finally, SMXL3- and aSMXL4-clade proteins, represented by SMXL3, SMXL4, and SMXL5 in Arabidopsis , regulate phloem development and anthocyanin abundance (Cho et al 2018; Wallner et al 2017, 2023; Wu et al 2017; Li et al 2024).…”
Section: Introductionmentioning
confidence: 99%